Volatile organic compounds produced by castor bean cake incorporated into the soil exhibit toxic activity against Meloidogyne incognita. Issue 2 (11th September 2018) - Pedroso, Luma A; Campos, Vicente P; Pedroso, Marcio P; Barros, Aline F; Freire, Eduardo S; Resende, Franciely MP
Abstract: Background: This study showed, for the first time, the effect of volatile organic compounds (VOCs) emitted by castor bean cake added to soil on the plant‐parasitic nematode Meloidogyne incognita . Identification of nematotoxic volatiles increases the chance of identifying molecules for use in commercial nematicides. Results: VOCs produced after the incorporation of castor bean cake in the soil resulted in immobility (>97.3%) and death (>96.9%) of M. incognita second‐stage juveniles (J2) and reduction in M. incognita egg‐hatch (>74.3%) at all concentrations of cake tested (1.5–6.0%). A similar reduction in M. incognita infectivity and reproduction was observed when nematodes were exposed to these VOCs and inoculated into tomato plants or exposed directly upon contact with the soil. We identified 32 VOCs produced by castor bean cake when incorporated into soil by using solid phase micro‐extraction gas chromatography coupled with mass spectrometry (SPME‐GC‐MS). Four of the most intense peaks in the chromatogram represented the compounds phenol, 4‐methylphenol, γ‐decalactone, and skatole. When M. incognita J2 were exposed to these compounds, all of the compounds demonstrated nematicidal activity with low median lethal concentration (LC50 ) values. Conclusion: Castor bean cake incorporated into the soil produces volatile compounds which are toxic to M. incognita . These substances show potential for application in the nematicide‐producing industry. © 2018 Society of Chemical Industry Abstract : Castor bean cake incorporated into the soil produces toxic volatiles to Meloidogyne incognita and four compounds show nematicidal activity against M. incognita .